2014
DOI: 10.1007/s10897-014-9707-6
|View full text |Cite
|
Sign up to set email alerts
|

Motivation to Pursue Genetic Testing in Individuals with a Personal or Family History of Cardiac Events or Sudden Cardiac Death

Abstract: Genetic testing is becoming increasingly available for cardiac channelopathies, such as long QT syndrome and Brugada syndrome, which can lead to sudden cardiac death. Test results can be used to shape an individual’s medical management and to identify at-risk family members. In our qualitative study, all participants had a personal or family history of a diagnosed cardiac arrhythmia syndrome or sudden cardiac death. Open-ended interviews were conducted individually and in focus groups. Interviews were audio re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 26 publications
(47 reference statements)
3
8
0
Order By: Relevance
“…This is in line with previous studies which found a high level of acceptance of genetic testing for the purposes of treatment and family [15,28]. These have also been endorsed as reasons to have genetic testing in other conditions including hereditary cardiac conditions and colorectal cancer [35,36].…”
Section: Discussionsupporting
confidence: 88%
“…This is in line with previous studies which found a high level of acceptance of genetic testing for the purposes of treatment and family [15,28]. These have also been endorsed as reasons to have genetic testing in other conditions including hereditary cardiac conditions and colorectal cancer [35,36].…”
Section: Discussionsupporting
confidence: 88%
“…This finding is consistent with studies done in the context of testing for hereditary diseases, as a primary motivation for genetic testing is the potential for personal and family benefit [30,31,32,33]. Those who rated living a healthy lifestyle as very important were also more likely to rate actionability as useful, suggesting that individuals who perceive greater control of their health through preventive behaviors (e.g.…”
Section: Discussionsupporting
confidence: 88%
“…Exploratory and pilot studies have identified interest in furthering research as among the primary reasons given for testing for genetic causes of sudden cardiac death, smoking susceptibility, deafness, and a variety of cancers [28][29][30][31][32]. For quantitative studies involving genetic tests for conditions including BRCA, Alzheimer's, and Pancreatitis, testing intention has previously been associated with wanting to help advance research [33][34][35][36][37].…”
Section: Doi: 107243/2054-992x-4-4mentioning
confidence: 99%